S1P receptor modulators affect the toxicity of amyloid β oligomers in microglial and neuronal cells - Iga Wieczorek; Robert P. Strosznajder (Folia Neuropathologica)
A large body of evidence has shown that the amyloid b peptide oligomers (Abo) are predominantly responsible for the neurodegeneration/cognitive impairments in Alzheimer’s disease (AD). Abo cause mitochondrial dysfunctions leading to an imbalance between pro- and antiapoptotic proteins and finally to neuronal apoptosis. Further, Abo trigger overactivation of microglia followed by enhanced release of proinflammatory cytokines, which exacerbates neurotoxicity of Abo. The above-mentioned alterations are accompanied by disturbed metabolism of prosurvival bioactive sphingolipid, sphingosine-1-phosphate (S1P), and S1P-dependent signalling via specific receptors (S1PR1-5). In the present study, we investigated for the first time the influence of selective – ponesimod (S1PR1), CYM5541 (S1PR3), CYM50308 (S1PR4), A971432 (S1PR4), siponimod (S1PR1,5) – and nonselective – phosphorylated fingolimod/pFTY720 (S1PR1,3-5) – S1P receptor modulators on cell viability, mitochondrial membrane potential (MMP) and expression of genes encoding S1P receptors, pro- and antiapoptotic proteins and proinflammatory cytokines in hippocampal neuronal (HT22) and in microglial (BV2) cell lines treated with 1 µM Abo for 24 hours. A significant reduction in the MMP, cell viability and mRNA levels of Bcl2 and Il18 together with increased Il6 expression was observed in HT22 cells after Abo administration. CYM50308 and A971432 restored the Bcl2 mRNA level to control values (those of Abo-untreated cells) and pFTY720 markedly reduced the Il6 expression. In BV2 cells, Abo induced a significant decrease in the MMP, cell viability and expression of S1pr1, Bad, Bcl2, Tnf and Il18, which was not counteracted by any of the modulators used. In turn, mRNA levels of Il1b, Il6, were markedly increased in microglia after Abo treatment and the administration of studied compounds tended to exacerbate the proinflammatory effect of Abo. In conclusion, the toxic effect of Abo is more pronounced in microglia. S1P receptor modulators may to some extent mitigate proapoptotic and proinflammatory effects of Abo in HT22 cells. In contrast, the same compounds tend to enhance Abo-induced inflammatory changes in BV2 cells.